Evaluasi Pelaksanaan Asesmen Nasional Berstandar Komputer di Madrasah Ibtidaiyah - Abdul Fitri Berlianto; Heldy Ramadhan Putra Pembangunan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
Improvement and evaluation of education is currently being carried out by the Indonesian government, namely by mapping the quality of education with a program called the National Assessment. The implementation of a computer-based National Assessment, abbreviated as ANBK (Computer-Based National Assessment) is an assessment of the quality of each education unit and equality program at the elementary and secondary levels with instruments in the form of Minimum Competency Assessment (AKM), character surveys, and learning environment surveys. The purpose of this study was to find out about the evaluation implementation of ANBK at the Tanjungsari Banyudono Muhammadiyah Elementary School. This research method uses a descriptive method with a qualitative approach. The results of this study are that the implementation of ANBK previously used the online ride-hailing mode which later became independent online the following year. After switching to independent online, it was accompanied by improvements in facilities and infrastructure such as increasing electrical power from originally 900 watts to 2,200 watts, internet speed from previously 10 Mbps to 20 Mbps and adding laptop devices, this was done for the smooth implementation of ANBK. The inhibiting factor for the implementation of ANBK is the limited number of laptops. Even though it had been attempted by borrowing the teacher's, it turned out that not all of the teacher's laptops were in good condition. While the supporting factors are the improvement of facilities and infrastructure such as increased power and internet speed, and students who have been provided with computer/laptop operation training long before the implementation of ANBK through ICT extracurricular activities.